MULTIPARENTALITY AND ITS LEGAL EFFECTS: AN ANALYSIS OF THE LEGAL AND SOCIAL IMPLICATIONS (REMUNOM, 2025)
Multiparentality emerges as a legal response to the increasing complexity of contemporary family structures, recognizing multiple socio-affective ties alongside biological ties, without hierarchy among them. The study begins with the problematic constraint of traditional normative frameworks which assume only one father and one mother and the challenge of adapting Family Law to factual family arrangements: how to reconcile registration and rights when an individual has more than two legal parents? The general objective of this research is to analyze the legal effects arising from the recognition of multiparentality, as well as its social consequences. Specific aims include: (i) mapping legal provisions and landmark case law that support multiparentality in Brazil; (ii) examining impacts on child support obligations, inheritance rights, custody, civil registration, and naming; (iii) identifying gaps and conflicts between doctrinal theory and practical application. A qualitative legal methodology is employed, including bibliographic research and analysis of emblematic judicial decisions (notably the RE 898.060/SC in the repercussão geral context) and statements from institutional bodies such as IBDFAM. It is found that the recognition of multiparentality yields full effects of kinship: concurrent child support obligations (across multiple parents), sharing of inheritance rights, multiplex registration entries, surname use rights, and implications for custody and visitation. The study concludes that, although the institute signifies significant progress in the constitutional protection of children (the principle of integral protection), interpretative and operational challenges remain particularly in inheritance law and coordinating duties among multiple parents. Legislative action is recommended to clarify criteria, along with improvements at registry and judiciary levels for uniformity of understanding.